The Influence of Google Score Ratings and Reviews on Vietnamese Consumers’ Online Hotel Booking Decision: A Case Study of Five-star Hotels in Vietnam - Le, Hau; Punnahitanond, Ratanasuda (Journal of Contemporary Social Sciences and Humanities, 2025)
This study investigates whether Google score ratings and Google reviews on four hotel characteristics, namely, Facilities, Location, Staff, and Services, influence Vietnamese consumers’ online booking decisions for the 5-star hotels in Vietnam. Samples were Vietnamese consumers in the Northern, Central, and Southern regions of Vietnam who booked the 5-star hotel online after reading Google score ratings and reviews. Online surveys were conducted with 300 participants using the self-administered questionnaire. Multiple Regression Analysis was undertaken to determine the impact of Google score ratings and reviews on Vietnamese consumers’ hotel booking decisions. The results from the analysis revealed that both Google score ratings and reviews on four hotel characteristics significantly influenced Vietnamese consumers’ online booking decisions. Interestingly, Google reviews on hotel services had the highest impact, followed by reviews on location, staff, and facilities.